Chitosan nanoparticles containing fusion protein (Hspx–PPE44–EsxV) and resiquimod adjuvant (HPERC) as a novel booster vaccine for Mycobacterium tuberculosis. (July 2022) - Hoseinpur, Rasul; Hasani, Alka; Baradaran, Behzad; Abdolalizadeh, Jalal; Amini, Yousef; Salehi, Roya; Samadi Kafil, Hossein; Azizian, Khalil; Memar, Mohammad Yousef; Gholizadeh, Pourya; Hasani, Akbar
This study attempted to explore the immunogenicity of chitosan nanoparticles containing fusion protein (Hspx–PPE44–EsxV; HPE) and resiquimod adjuvant (HPERC) in BALB/c mice. HPE was initially expressed in E. coli BL21 cells. HPE and resiquimod adjuvant were then encapsulated in chitosan nanoparticles (HPERC). One group of mice were subcutaneously vaccinated on days 0, 14, and 28 with HPERC, and the other group was primed with bacilli Calmette-Guérin (BCG) on day 0 and then boosted with HPERC on days 14 and 28. Two weeks after the last injection, IFN-γ, IL-4, and IL-17 in spleen cell culture supernatants, and IgG2a and IgG1 titers in sera were measured. HPERC size was 130.84 ± 12.08 nm ( n = 5). Zeta potential of HPERC was 29 ± 4 mv. The highest IFN-γ concentration was detected in BCG-primed mice that were boosted with HPERC. In addition, IL-17 production was significantly increased in all groups compared with that of control, except in those that received nanoparticle (NP), adjuvant (ADJ), NP/ADJ, and fusion protein (Hspx–PPE44–EsxV) (HPE). Comparison of IFN-γ and IL-4 concentration determined that Th1 was activated in BCG-primed and HPERC-boosted group in comparison to the other groups. No significant difference in concentration of IL-4 was observed between groups receiving HPERC and BCG-primed and HPERC-boosted group in comparison to group BCG. Concentrations of IgG2a and IgG1 also increased compared to the control group and the rate of IgG2a was higher compared to IgG1. Chitosan containing HPERC vaccine could induce a high level of specific cytokines in mice. The group of mice which first received BCG and then HPERC as booster vaccine could produce significant amounts of IFN-γ, IL-17, and IgG2a.